2013
DOI: 10.1101/gr.153510.112
|View full text |Cite
|
Sign up to set email alerts
|

The maize methylome influences mRNA splice sites and reveals widespread paramutation-like switches guided by small RNA

Abstract: The maize genome, with its large complement of transposons and repeats, is a paradigm for the study of epigenetic mechanisms such as paramutation and imprinting. Here, we present the genome-wide map of cytosine methylation for two maize inbred lines, B73 and Mo17. CG (65%) and CHG (50%) methylation (where H = A, C, or T) is highest in transposons, while CHH (5%) methylation is likely guided by 24-nt, but not 21-nt, small interfering RNAs (siRNAs). Correlations with methylation patterns suggest that CG methylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

34
316
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(355 citation statements)
references
References 49 publications
(62 reference statements)
34
316
1
Order By: Relevance
“…7B). The difference in specificity of splicing factor gene expression changes compared with splicing changes likely arises due to the influence of other factors on splicing, such as transcription rate or methylation status (Kornblihtt et al, 2004;Shepard and Hertel, 2008;Regulski et al, 2013). It has been shown previously that splicing factors are frequently alternatively spliced, often resulting in increased or decreased NMD sensitivity (Lareau and Brenner, 2015).…”
Section: Changes In Splicing Correlate With Gene Expression Changes Imentioning
confidence: 99%
See 2 more Smart Citations
“…7B). The difference in specificity of splicing factor gene expression changes compared with splicing changes likely arises due to the influence of other factors on splicing, such as transcription rate or methylation status (Kornblihtt et al, 2004;Shepard and Hertel, 2008;Regulski et al, 2013). It has been shown previously that splicing factors are frequently alternatively spliced, often resulting in increased or decreased NMD sensitivity (Lareau and Brenner, 2015).…”
Section: Changes In Splicing Correlate With Gene Expression Changes Imentioning
confidence: 99%
“…Gene expression changes in splicing factors also play key roles in guiding tissuespecific developmental processes, including seed development, where the U2AF splicing factor ROUGH ENDOSPERM3 has been shown to be involved in mediating the interaction between the embryo and endosperm (Fouquet et al, 2011). The control of these alternative splicing differences among different tissues is thought to be the result of differential splicing factor expression and is likely also influenced by tissue-specific methylation patterns (Regulski et al, 2013). Alternative splicing has also been tied closely with nonsensemediated decay (NMD) and has been shown to increase or decrease a transcript's sensitivity to this decay mechanism under a variety of conditions (Kalyna et al, 2012;Drechsel et al, 2013;Staiger and Brown, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that alteration of the DNA methylation status in these genes can change the activities of the anthocyanin biosynthetic pathway. Furthermore, genome-wide methylome analysis in maize and rice has suggested that the DNA methylation in the promoter region often represses gene expression, whereas moderate gene-body methylation has a positive effect on the gene expression (Li et al, 2012;Regulski et al, 2013). Therefore, DNA methylation status may affect gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Plant DNA methylation is known to play an important role in genomic imprinting and genomic protection from transposable elements (TEs) and other repetitive DNA sequences. Furthermore, it regulates the expression of multiple genes (Jaenisch and Bird, 2003) and has been implied to play a role in gene splicing (Regulski et al, 2013). The influence of DNA methylation on development is especially evident in the case of mutations in DMT genes, which are embryo lethal in mice and lead to developmental abnormalities in plants (Goll and Bestor, 2005).…”
mentioning
confidence: 99%